1993
DOI: 10.1126/science.7694361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Alternative CTLA-4 Ligand Costimulatory for T Cell Activation

Abstract: Stimulation of T cell proliferation generally requires two signals: The first signal is provided by the T cell receptor binding to antigen, and the second signal or costimulus is provided by a different receptor-ligand interaction. In mouse and human, the CD28-B7 interaction has been identified as a source of costimulatory signals. We have identified a cell surface molecule (GL1) that is distinct from B7 and abundantly expressed on activated B cells. On activated B cells GL1, rather than B7, is the predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(271 citation statements)
references
References 14 publications
4
266
1
Order By: Relevance
“…With regard to in vivo relevance, a number of studies have suggested that antigen presentation by resting B cells causes T cell anergy instead of priming (33,34). This finding is of particular interest because resting B cells express high levels of ICAM-1 but minimal levels of B7 (35). Even for dendritic cells, it is notable that immature subsets can express low levels of B7 with significant levels of ICAM-1 (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to in vivo relevance, a number of studies have suggested that antigen presentation by resting B cells causes T cell anergy instead of priming (33,34). This finding is of particular interest because resting B cells express high levels of ICAM-1 but minimal levels of B7 (35). Even for dendritic cells, it is notable that immature subsets can express low levels of B7 with significant levels of ICAM-1 (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…5. Similar to the effects of a-CTLA-4 antibodies, the injection of 250 mg each of a-B7-1 and a-B7-2 antibodies, known to block the ligands for CTLA-4 and CD28 (20,21), resulted in higher average pmel-1 Each data point represents a cell, and the population mean is indicated by a black bar. Data are pooled from at least three independent experiments.…”
Section: Effects Of Other Antibodies On Pmel-1 Dynamics In Tdlnsmentioning
confidence: 96%
“…In addition, full activation of these cells requires the binding of costimulatory molecules expressed on one cell to costimulatory molecules expressed on the other (3,4). One such costimulatory molecule is CD86 (B7-2), which is expressed at a low level on a resting B cell (5,6), but is up-regulated following the stimulation of BCR (7,8), CD40 (9,10), MHC class II (11), LPS receptor (5,7,12,13), IL-4R (14,15), and/or ␤ 2 -adrenergic receptor (␤ 2 AR) (16,17). CD86 binds to the costimulatory molecule CD28 on the Th cell to increase the expression of the costimulatory molecule CD40 ligand (CD40L) on the Th cell and also to increase the level of cytokine produced by the Th cell (13,15,18).…”
Section: Selective Regulation Of Mature Igg1 Transcription By Cd86mentioning
confidence: 99%